Mengenal Tafsir Nusantara: Melacak Mata Rantai Tafsir Dari Indonesia, Malaysia, Thailand, Singapura Hingga Brunei Darussalam - Hasani Ahmad Said (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2017)
Tafsir (exegesis) scholars traced in the Nusantara archipelago, will not be separated from the figure of ‘Abdurrauf al-Fansuri with his Tarjuman alMustafid. Through this work, tafsir had been developed through many media teaching until today. This work also allegedly gave birth to a variety of tafsir model and methodology of qur’anic interpretation in the archipelago. At least two aspects of the interpretation gives birth to the scholars transmission; and to development of the science of interpretation. Firstly, through the activities of teaching; and secondly, through writings. Through these two transmission lines the network of interpretation, until today continues to progress well.